DEVELOPING AN ATUTOMATIC U-SHAPED TOOTHBRUSH FOR CHILDREDN WITH SPECIAL NEEDS - Valendriyani Ningrum; Abu Bakar; Ricki Ananda (Smart Education, 2025)
Abstract: Various types of toothbrushes are available for children with special needs, including manual toothbrushes with modified handles, electric toothbrushes, and U-shaped manual toothbrushes. Each toothbrush has inherent limitations that result in suboptimal tooth cleaning, particularly in children with mental disorders and/or fine motor skills. The objective of this study is to develop the potential of an automatic U-shaped toothbrush designed to address the specific oral hygiene needs of children with disabilities. The key scientific concepts that underpin the development of an automatic U-shaped toothbrush is an effective toothbrush for children with special needs, which is easy to use and optimal in removing debris and/or dental plaque. The results of the development of this study produced a prototype scale of the U-shaped toothbrush that simply by pressing one button can clean the entire surface of the teeth on the upper or lower jaw. In conclusion, this automatic U-shaped toothbrush is expected to be beneficial for children with poor fine motor skills, intellectual disabilities, or other special needs who have had difficulty cleaning their teeth properly. Keywords: Automatic, Children, Special Needs, Toothbrush, U-Shaped Abstrak: Berbagai jenis sikat gigi tersedia untuk anak-anak dengan kebutuhan khusus, termasuk sikat gigi manual dengan gagang yang dimodifikasi, sikat gigi elektrik, dan sikat gigi manual berbentuk U. Setiap sikat gigi memiliki keterbatasan bawaan yang mengakibatkan pembersihan gigi kurang optimal, terutama pada anak-anak dengan gangguan mental dan/atau keterampilan motorik halus. Tujuan dari penelitian ini adalah untuk mengembangkan potensi sikat gigi otomatis berbentuk U yang dirancang untuk memenuhi kebutuhan kebersihan mulut khusus pada anak-anak dengan disabilitas. Konsep ilmiah utama yang mendasari pengembangan sikat gigi otomatis berbentuk U ini adalah menghasilkan sikat gigi yang efektif untuk anak-anak dengan kebutuhan khusus, mudah digunakan, dan optimal dalam menghilangkan sisa makanan dan/atau plak gigi. Hasil pengembangan dari penelitian ini menghasilkan prototipe sikat gigi berbentuk U skala percobaan yang hanya dengan menekan satu tombol dapat membersihkan seluruh permukaan gigi pada rahang atas atau bawah. Sebagai kesimpulan, sikat gigi otomatis berbentuk U ini diharapkan bermanfaat bagi anak-anak dengan keterampilan motorik halus yang rendah, disabilitas intelektual, atau kebutuhan khusus lainnya yang mengalami kesulitan dalam membersihkan gigi dengan benar. Kata kunci: Otomatisasi, Anak, Kebutuhan Khusus, Sikat Gigi, Berbentuk U